1-(2,4-dihydroxyphenyl)ethanone (1H-indol-3-yl)acetyl hydrazone-2-(1H-indol-3-yl)aceto-hydrazide(1/1) - Ali, Hapipah Mohd; Ng, S.W.; Jefrey, B.W.; Zuraini, K. (International Union of Crystallography, 2007)
The two components of the title cocrystal, C10H10N3O center dot C18H18N3O3, are linked by a hydrazine-hydroxy N-H center dot center dot center dot O hydrogen bond; an intermolecular amide-amide N-H center dot center dot center dot O interaction that involves only the hydrazide component leads to the formation of a linear chain structure. Further intermolecular O-H center dot center dot center dot O and N-H center dot center dot center dot O hydrogen bonds form a two-dimensional network.